Antipsychotic use and unexpected death: a hospital‐based case–control study. (25th September 2015) - Mace, S.; Dzahini, O.; Cornelius, V.; Anthony, D.; Stewart, R.; Taylor, D.
Abstract : Objective: To examine the risk of unexpected death in patients prescribed an antipsychotic. Unexpected death was defined as death occurring within 7 days of the onset of acute symptoms. Method: A case–control study conducted on events occurring between July 2009 and January 2011 in a UK mental health trust providing in‐patient and out‐patient services. Results: The study included 100 cases (deaths) and 436 unmatched controls. Current users of antipsychotics had a lower risk of unexpected death than non‐users – adjusted odds ratio (OR) 0.48 (95% CI 0.24–0.94, P = 0.033). A significant reduction in risk was seen for second‐generation [adjusted OR 0.42 (95% CI 0.21–0.86, P = 0.018)], but not first‐generation agents [adjusted OR 0.83 (95% CI 0.31–2.20, P = 0.706)]. Treatment with antipsychotics for any duration was associated with reduced risk. Dose and route of administration did not affect risk. In a planned secondary analysis not adjusting for cardiovascular disease, prescription of an antipsychotic was not associated with increased risk of unexpected death [adjusted OR 0.56 (95% CI 0.28–1.08, P = 0.084)]. Conclusion: Our findings do not support an association between current antipsychotic use and increased risk of unexpected death.